Q23 A double blind, cross over, placebo-controlled, phase II trial of Sativex in Huntington's Disease. (29th August 2012) - Caldentey, JG; Lopéz-Sendón, JL; Trigo, P; Ruiz, C; Ribas, GG; Aguilar, M; Galvez, MA; Pablo, I; Galve-Roth, I; Sagredo, O; Fernandez-Ruiz, JJ; Guzman, M; et al.
Abstract : Background: Cannabinoid are involved in Huntington's disease (HD) and cannabinoid stimulation improves the deficits in models of HD, suggesting promising effects in HD. Methods: We conducted a double blind, cross over, placebo-controlled, phase II trial of SATIVEX* (a combination of plant extracts enriched in Δ9-tetrahydrocannabinol and cannabidiol) in patients with HD. SATIVEX and placebo were dispensed as an oral spray, up to 12 sprays/day. The primary end point was safety, evaluated as (a) absence of severe adverse events and (b) no greater deterioration of motor, cognitive, behavioural and functional UHDRS scales during the phase of active treatment. Secondary end points included the levels of neurotrophic factors, citokines, pro-and antiapoptotic proteins in blood and cerebrospinal fluid, the proteasome function, autophagy and resistance to neurotoxins in patients' fibroblasts. Results: 26 patients were screened and 25 randomised. One patient withdrew the consent due to lack of improvement. 24 patients completed the trial. No serious adverse events were considered related to the medication. One patient developed anaemia related to gastrointestinal bleeding and got pregnant after completing the active treatment. Another patient had asymptomatic spinal fluid leucocytosis. The majority of the subjects reached the maximal recommended daily dose with good tolerance. Although still blinded, 19 patients had a differential score of more than 4 points in the Motor-UHDRS scale during the two trial phases. The sleep quality and anxiety improved in most patients in one phase of the trial. We obtained hundreds of aliquots of blood, lymphocytes, cerebrospinal fluid and fibroblasts for biomarker analysis. Conclusions: The treatment with Sativex is safe for patients with HD and appears to have beneficial effects on patients symptoms. The significancy of these effects and the effects on biomarkers will be studied in the next months. Funding: Supported by GW Pharmaceuticals, MICINN2011, CAIBER and CIBERNED.